Pengaruh Brand Trust, Cita Rasa, dan Social Media Influencer terhadap Keputusan Pembelian - Arviliasih Arviliasih; Bayu Pramutoko; Ustadus Sholihin (STIKes Ibnu Sina Ajibarang, 2025)
Competition in the local culinary business is getting fiercer as consumers become more selective in choosing products based on quality, experience, and social media influence. Nasi Uduk Pemuda in Doko Village, Kediri Regency, is one of the culinary businesses that strives to survive by leveraging brand trust, distinctive flavors, and promotions through social media influencers. This study aims to analyze the extent to which brand trust, flavor, and social media influencers influence consumer purchasing decisions. The research method used is quantitative with a survey approach to consumers who have purchased the product. The number of samples was determined using the Slovin formula to ensure representativeness. Data collection was carried out through questionnaires, then analyzed using SPSS 29 software. The analysis included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial t-tests, simultaneous f-tests, and calculation of the coefficient of determination (R²). The results show that partially, brand trust has a positive and significant influence on purchasing decisions, as does the taste variable, which has been shown to play an important role in driving consumer loyalty and repurchase intention. Meanwhile, promotion through social media influencers showed a positive but insignificant influence, indicating that the presence of influencers does not fully determine consumer decisions in the context of traditional culinary products. The f-test showed that all three variables simultaneously had a significant influence on purchasing decisions. The coefficient of determination (R²) value of 0.669 indicates that 66.9% of the variation in purchasing decisions can be explained by brand trust, taste, and social media influencers, while the remainder is influenced by other factors outside the study. This finding emphasizes the importance of maintaining consistent product quality, building brand trust, and continuing to utilize social media strategically as an effort to increase the competitiveness of local culinary businesses.